Early 20th Century Projects for Construction of Transportation Corridors to Rich Mineral Resources of Yakutia - N. I. Burnasheva; I. I. Kovlekov (Научный диалог)
This article presents an analysis of early 20th-century projects aimed at constructing a railway and establishing transportation routes connecting Yakutia to the Siberian railway network. The historical sources for this research include documents from the Russian State Archive of Economics and articles published in periodicals in 1912 and 1925. The study reveals that the first railway project predominantly planned to traverse Yakutia was proposed by French national Loïc de Lobel, who envisioned the Trans-Alaska-Siberia route between 1902 and 1907. It is emphasized that, following a series of government discussions, de Lobel’s proposal was ultimately rejected due to concerns about the undesirable exploitation of the region’s natural and mineral resources by foreign capital. The findings indicate that de Lobel’s project served as a catalyst for initiating the development of transportation projects intended to connect Yakutia with the Siberian railway. Overall, the public announcement and discussion of transportation construction projects in the early 20th century played a positive role in the economic development of Russia’s peripheral regions.